Integrating quantitative and qualitative methodologies for the assessment of health care systems: emergency medicine in post-conflict Serbia - VanRooyen Michael J; Milić Ljiljana; Vuksanović Miloš; Mitrović Mihajlo; Šćepanović Milena; Dierberg Kerry; Nelson Brett D (BMC, 2005)
Abstract Background Due to the complexity of health system reform in the post-conflict, post-disaster, and development settings, attempts to restructure health services are fraught with pitfalls that are often unanticipated because of inadequate preliminary assessments. Our proposed Integrated Multimodal Assessment - combining quantitative and qualitative methodologies - may provide a more robust mechanism for identifying programmatic priorities and critical barriers for appropriate and sustainable health system interventions. The purpose of this study is to describe this novel multimodal assessment using emergency medicine in post-conflict Serbia as a model. Methods Integrated quantitative and qualitative methodologies - system characterization and observation, focus group discussions, free-response questionnaires, and by-person factor analysis - were used to identify needs, problems, and potential barriers to the development of emergency medicine in Serbia. Participants included emergency and pre-hospital personnel from all emergency medical institutions in Belgrade. Results Demographic data indicate a loosely ordered network of part-time emergency departments supported by 24-hour pre-hospital services and an academic emergency center. Focus groups and questionnaires reveal significant impediments to delivery of care and suggest development priorities. By-person factor analysis subsequently divides respondents into distinctive attitudinal types, compares participant opinions, and identifies programmatic priorities. Conclusions By combining quantitative and qualitative methodologies, our Integrated Multimodal Assessment identified critical needs and barriers to emergency medicine development in Serbia and may serve as a model for future health system assessments in post-conflict, post-disaster, and development settings.